Two new taxa of Piper (Piperaceae) from Kerala, India with a note on their origin and interrelationships - RAVINDRAN, K NIRMAL BABU, V GIRISH NAIK, P N (Journal of Spices and Aromatic Crops, 1993)
Two new taxa of Piper, P. sugandhi and P. sugandhi var. breuipilis are described from Sugandhagiri project area of Western Ghats in South India. They are related to Piper nigrum, P. galeatum and P. trichostachyon. Morphological and ecological evidences point to their origin through hybridisation involving these three species. Their inter-relationships are discussed.